2004
DOI: 10.2134/jeq2004.2320
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Mobility of Linear Alkylbenzene Sulfonate and Nonylphenol in Sludge‐Amended Soil

Abstract: Degradation and mobility of the surfactants linear alkylbenzene sulfonate (LAS) and nonylphenol (NP) were investigated in a lysimeter study using a sandy loam soil and 45-cm soil columns. Anaerobically digested sewage sludge was incorporated in the top-15-cm soil layer to an initial content of 38 mg LAS and 0.56 mg NP kg(-1) dry wt., respectively. Spring barley (Hordeum vulgare L.) was sown onto the columns. The lysimeters were placed outdoors and therefore received natural precipitation, but were also irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Vogel et al (2003) showed that NP leaching is extremely limited, since most NP was found within the first 30 cm of the surface. Jacobsen et al (2004) also indicated that downward transport of NP was negligible in a lysimeter experiment. However, the slight solubility of NP might allow some leaching and some bioavailability of this chemical (Brix et al 2001).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Vogel et al (2003) showed that NP leaching is extremely limited, since most NP was found within the first 30 cm of the surface. Jacobsen et al (2004) also indicated that downward transport of NP was negligible in a lysimeter experiment. However, the slight solubility of NP might allow some leaching and some bioavailability of this chemical (Brix et al 2001).…”
Section: Introductionmentioning
confidence: 93%
“…Sjöström et al (2008) reported half-lifes in different soils of around 7-20 days for NP and 5-30 days for NP12EO. Jacobsen et al (2004), in an outdoor lysimeter experiment, reported a 45% decline in NP concentration following amendment with sludge after only 10 days, while NP was undetectable after 110 days. Petersen et al (2003) in agricultural amendments with sewage sludge with low levels of NP, failed to find detectable concentrations of NP 200 days after the application.…”
Section: Introductionmentioning
confidence: 98%
“…2b). The poor downward transport of LAS in soil and sediments has been often reported in the previous literature (León et al 2001;Jacobsen et al 2004). The maximal concentration of the surfactant was measured in the upper fractions of the LAS50 microcosms after 7 days and widely exceeded those reached in soil after sludge amendment (Jensen et al 2007).…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, these methodologies present several disadvantages, such as the high extraction time for Soxhlet (8-24 h) or the large volumes of solvents needed ($200 ml for Soxhlet and 50-150 ml for ultrasound). Modern extraction procedures such as pressure liquid extraction (PLE) [7,15,20,22], microwaveassisted extraction (MAE) [12,30], supercritical fluid extraction (SFE) [31], or ultrasonic extraction [11,32] are being used as alternatives because of their high efficiency within shorter extraction times (5-10 min) and the lower solvent volume needed (5-20 ml). However, some of these methodologies are tedious, time consuming, and require one or two solidphase extraction (SPE) steps for concentration and cleanup of samples.…”
Section: Introductionmentioning
confidence: 99%